Selectivity switching resulting in the formation of benzene by surface carbonates on ceria in catalytic gas-phase oxidation of benzyl alcohol. Issue 13 (18th January 2016) - Dai, Yihu; Wu, Xin-Ping; Tang, Yu; Yang, Yanhui; Gong, Xue-Qing; Fan, Jie
Abstract : The carbonate deposits on CeO2 cause the formation of benzene in gas-phase aerobic oxidation of benzyl alcohol via easy trapping of CO fragments. Abstract : The irreversible formation of carbonate deposits on CeO2 leads to complete switching of catalytic selectivity resulting in the formation of benzene in gas-phase oxidation of benzyl alcohol. By integrating experimental spectra and theoretical calculations, we expect that such a shift is derived from further decarbonylation of benzaldehyde via easy trapping of CO fragments by surface carbonate species.